PS-023 Medical acceptance of sequential treatment. (24th February 2014) - Fraile, MJ; Gozalo, I; Miralles, J; Barrero, A; Batlle, M; Castells, M; Garcia, T; Hernández, D; Ruiz, C; Killick, A
Abstract : Background: Administering treatment by the right route improves patient safety and reduces healthcare spending. Purpose: To assess the medical acceptance of sequential treatment (ST) proposals made by the pharmacy in accordance with agreed guidelines and to evaluate the cost savings. Materials and methods: For 2 months, the pharmacist twice a week, recorded patients continuing intravenous antibiotic treatment for more than 72 h. Following clinical and analytical standards previously accepted by the Drugs Committee, each patient was evaluated, and if they complied with all aspects necessary to make the transition to oral treatment, this was recommended to the doctor in the clinical record. The antibiotics that were analysed were those with high bioavailability. Results: Over two months we noted 76 patients, but only 16 met the requirements for treatment change. The rest of the patients, 60 (79%), were not candidates for oral treatment due to: Fasting treatment (35%) Discharge of patients from hospital (31.6%) Altered lab test results (23.3%) Palliative care (5%) Death of patient (1.7%) To ensure patient compliance (1.7%) Diagnosis did not favour a change of treatment (1.7%) Conclusions: The level of medical acceptance of the ST was high (76.9%), but the percentage of patient candidates was low (21%) because the average hospital stay is short (5.9 days) and the majority of patients had altered gastrointestinal absorption. Amoxicillin/clavulanic acid was the antibiotic most often administered orally, but more money was saved (275.26 €) by changing to oral treatment with fluoroquinolones. No conflict of interest.